Improved Accuracy of Minimally Invasive Transpedicular Screw Placement in the Lumbar Spine With 3-Dimensional Stereotactic Image Guidance: A Comparative Meta-Analysis. Issue 9 (November 2015) - Unknown
Abstract : Study Design: This study compares the accuracy rates of lumbar percutaneous pedicle screw placement (PPSP) using either 2-dimensional (2-D) fluoroscopic guidance or 3-dimensional (3-D) stereotactic navigation in the setting of minimally invasive spine surgery (MISS). This represents the largest single-operator study of its kind and first comprehensive review of 3-D stereotactic navigation in the setting of MISS. Objective: To examine differences in accuracy of lumbar pedicle screw placement using 2-D fluoroscopic navigation and 3-D stereotaxis in the setting of MISS. Summary of Background Data: Surgeons increasingly rely upon advanced image guidance systems to guide minimally invasive PPSP. Three-dimensional stereotactic navigation with intraoperative computed tomography offers well-documented benefit in open surgical approaches. However, the utility of 3-D stereotaxis in the setting of MISS remains incompletely explored by few studies with limited patient numbers. Materials and Methods: A total of 599 consecutive patients underwent minimally invasive lumbar PPSP aided by 3-D stereotactic navigation. Postoperative imaging and medical records were analyzed for patient demographics, incidence and degree of pedicle breach, and other surgical complications. A total of 2132 screw were reviewed and compared with a meta-analysis created from published data regarding the placement of 4248 fluoroscopically navigated pedicle screws in the setting of MISS. Results: In the 3-D navigation group, a total of 7 pedicle breaches occurred in 6 patients, corresponding to a per-person breach rate of 1.15% (6/518) and a per-screw breach rate of 0.33% (7/2132). Meta-analysis comprised of data from 10 independent studies showed overall breach risk of 13.1% when 2-D fluoroscopic navigation was utilized in MISS. This translates to a 99% decrease in odds of breach in the 3-D navigation technique versus the traditional 2-D-guided technique, with an odds ratio of 0.01, (95% confidence interval, 0.01–0.03), P <0.001. Conclusions: Three-dimensional stereotactic navigation based upon intraoperative computed tomography imaging offers markedly improved accuracy of percutaneous lumbar pedicle screw placement when used in the setting of MISS.